ROLE OF PERFORMANCE IMPROVEMENT MEASURES TO IMPROVE THE QUALITY OF INFECTION PREVENTION PROGRAMS IN TERTIARY CARE HOSPITAL - HUSSAIN , F; IRUM , S; HAIDER , DA; DIN , SU; MUBASHIR , M; NAQVI , M (Biological and Clinical Sciences Research Journal, 2024)
Healthcare-associated infections (HAIs) pose a significant risk in hospital settings. Performance improvement measures can enhance the quality of infection prevention programs, leading to better outcomes for patients. Objective: To assess the impact of performance improvement measures on enhancing the quality of infection prevention programs in a tertiary care hospital. Methods: This quasi-experimental study was conducted with healthcare workers (HCWs), including doctors, nurses, infection prevention officers, and support staff, at a tertiary care hospital. The intervention included comprehensive performance improvement measures: rigorous training, educational initiatives, regular audits with feedback, adherence to standard operating procedures (SOPs), checklists, monitoring tools, and hand hygiene promotion. Quantitative data on infection rates, infection control compliance, hand hygiene adherence, and antibiotic usage were collected at baseline and 3, 6, and 12 months post-intervention. Qualitative data were gathered from semi-structured interviews and focus groups to explore barriers and facilitators to infection prevention. Results: The intervention group showed a significant reduction in HAIs per 1,000 patient days compared to the control group (3.06 ± 1.09 vs. 8.23 ± 5.18; p = 0.00). Compliance with infection control practices (71.0% vs. 61.0%; p = 0.13) and hand hygiene adherence (64.0% vs. 48.0%; p = 0.02) were also higher in the intervention group. However, no statistically significant difference in antibiotic usage was observed between the two groups (59.0% vs. 49.0%; p = 0.1). Conclusion: The study demonstrates that performance improvement measures significantly reduce HAIs and improve compliance with infection control protocols. These targeted strategies are essential for enhancing infection prevention in healthcare settings and improving overall patient safety.